Desain Virtual Reality Wisata Kota Medan Pada Era Society 5.0: Desain Virtual Reality Wisata Kota Medan Pada Era Society 5.0 - Andi Supriadi Chan (ABEC Indonesia, 2021)
Medan city is the third largest city in Indonesia, various tribes and ethnicities inhabit this city and have lived side by side from the past. So that the city of Medan has various kinds of relics that are used as tourist attractions. The COVID-19 pandemic has caused a fall in the number of tourist visits and the lack of promotional facilities for potential tourists who will visit. The important circumstances of this condition prompted the research team to participate in Medan City Tourism Empowerment in the Era of Society 5.0 based on Virtual Reality during the COVID-19 pandemic. This study aims to design a tourist attraction in the city of Medan to be based on Virtual Reality. as one of the efforts of researchers in developing new tourism concepts in the midst of a pandemic and as a form of promotion with different concepts. The research method used is a combination method. Qualitatively, data collection was done through literature study, observation, and interviews. While quantitatively, a survey was conducted by distributing questionnaires to determine the public's perception of the use of VR technology for tourism, especially in terms of designing Virtual Reality 3600, using the MDCL design model in building VR applications. The results of the application are then tested so that they can be used as VR-based tourism content in Medan city tourism.